The influence of service quality and customer satisfaction on customer loyalty in E-Commerce settings - Chong, Albert Yan Vun (2011)
This study aims to determine the influence of service quality and customer satisfaction on customer loyalty in electronic commerce settings among professionals working in Sabah. The objectives of this study can be achieved by examining the relationship between customer loyalty and e-service quality (efficiency, requirement fulfillment, accessibility, privacy, and responsiveness) and customer satisfaction. Secondly, relationship between customer satisfaction and e-service quality. Thirdly, the relationship between customer satisfaction and customer loyalty and lastly, the mediating effects of customer satisfaction between e-service quality and customer loyalty. Data collection was conducted through questionnaire and a total of 292 questionnaires were collected out of 381 copies distributed. The results from the analysis obtained from the data collected shows that 76.04% of the variance are able to be explained by the research model. E-service quality of efficiency, privacy and responsiveness produces a Significant result while others appear to be insignificant. Customer satisfaction with service quality were found to have significant relationship on customer loyalty. Lastly, customer satisfaction were found to have significant mediating relationship between service quality and customer loyalty, whereby efficiency, privacy and responsiveness were found to be partially mediated. Further research is still needed to be done in order to understand the trend of the general online consumers instead of focusing on professionals only